PENGARUH MODEL FLIPPED CLASSROOM TERHADAP SELF-CONFIDENCE DAN HASIL BELAJAR SISWA SMAN 8 PONTIANAK - Pratiwi, Astri; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractSelf-confidence and learning achievement of XI MIPA students at SMAN 8 Pontianak were still unsatisfactory. This research was conducted to determine whether there was a significant difference between self-confidence of students taught using flipped classroom and conventional learning model, and whether there was a significant difference between learning achievement of students taught using flipped classroom and conventional learning model, and to determine effect size of flipped classroom learning model toward student self-confidence and learning achievement on solubility and solubility product. This research used quasi experimental with Nonequivalent Control Group Design. The research sample consisted of XI MIPA 1 class as the control group and XI MIPA 4 class as the experimental group selected by purposive sampling technique. Learning achievement test, self-confidence questionnaire, observation sheet and interview guidelines were used to collect data. Based on final questionnaire and posttest data analysis using the Mann-Whitney U-test (? = 5%), Asymp.Sig (2-tailed) were 0.000 and 0.017 respectively. This indicated that there were a significant difference between self-confidence and learning achievement of students taught using flipped classroom and conventional learning model. Flipped classroom learning model gave 29.96% effect toward self-confidence and 27.04% toward student learning achievement. Keywords:  Flipped classroom Learning Model, Self-Confidence, Learning Achievement, Solubility and Solubility Product